ANALISIS HUBUNGAN SIKAP PRIBADI DAN HARMONISASI KERJA PADA KANTOR KECAMATAN GUNUNGSITOLI ALO’OA KOTA GUNUNGSITOLI - JASAMANTRIN LAOLI; DELIPITER LASE; SUKA'ARO WARUWU (JURNAL ILMIAH SIMANTEK, 2022)
This study aims to analyze the relationship between personal attitudes and work harmonization at the Gunungsitoli Alo'oa District Office. This research was conducted at the Gunungsitoli Alo'oa District Office. Sampling was carried out by taking the total population, namely as many as 15 employees. The variables in this study are work attitudes (X) and employee harmonization (Y). The data collection technique is by observing and interviewing all samples. The data analysis technique in this study is by collecting data, presenting data, and drawing conclusions. The results of the study show that the relationship between personal attitudes and work harmonization of employees of the Gunungsitoli Alo'oa District Office is regulated by government regulations namely, government regulation No.42 of 2004 article 1 paragraph 2 and Republic of Indonesia Government regulation Number 53 of 2010 concerning Civil Servant Discipline.